Sentiment Polarity of Programmers in an Open Source Software Project: An Exploratory Study - Carigé, Rui Santos; Carneiro, Glauco de Figueiredo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Context: During the implementation of issues filed in open source software projects, programmers engage and interact in discussions on how to implement them. These discussions provide evidence to investigate emotionally loaded practices embraced by programmers. They interact to explain their point of view regarding the project and the issue under analysis. Objective: Analyze programmers sentiment polarity in an open source software project having releases as a reference for the analysis. Methods: We conducted an exploratory study to characterize the sentiment polarity of comments registered in issues associated with releases of the Moby open source software project. Results: The quantitative analysis identified sentiment polarity variations throughout consecutive releases in line with specific functionalities. Based on a qualitative analysis, we identified these functionalities and specific group of programmers that contributed to those results. Conclusions: We identified initial evidence to contribute for the understanding of the causes underlying the influence of the sentiments of the developers in the context of releases of open source software projects.